Symbolic Meaning of Batik In Madura Bridal Kebaya Clothes - Soelistyowati Soelistyowati; I Wayan Mudra; I Ketut Muka; Tjok Istri Ratna (Syntax Corporation Indonesia, 2023)
This study was conducted to determine the meaning of the batik symbol on the Madurese bridal kebaya. At weddings, Madurese people wear batik and kebaya, especially for women getting married. Madurese batik motifs are classified as having the characteristics of plant (vegetal) motifs, animals and geometric shapes. The influence on the Madurese batik motifs is the mixing of Javanese-Hindu, Chinese and Dutch cultures. Chinese mythology dominates the fenghuang bird and dragon motifs believed to have philosophy in each symbol. Bright and bold colors are characteristic of Madurese batik, such as red, black, yellow and green. This research approach using literature study is done by looking for references that are relevant to the cases or problems found using the semiotic theory of Charles Sanders Peirce. By analyzing the data of this study, it was carried out by means of 5W1H, what, where, when, why, who, and how. The results of this study, a. The icon as a sign of the message using the kebaya dress interprets the kebaya as an Indonesian woman who is elegant, feminine and has manners, as a procession that is carried out is a cultural carnival procession as a mandatory dress that must be worn. b) symbols, the colors red, black, yellow and green on the decoration, as well as the appearance of the dragon and fenghuang bird motifs are characteristic of batik motifs, on the jarik or sarong worn at traditional wedding ceremonies in Madura. c) Index: Madurese philosophy considers that the colors red and black are courage and assertiveness, yellow symbolizes abundance and green means religious. The dragon motif brings fortune, guards and is authoritative. The fenghuang bird in batik means honesty and thoroughness, tolerance, knowledge, loyalty and integrity. When the dragon is juxtaposed with the fenghuang bird, it symbolizes bringing luck, honesty, happiness and repellent to evil, which is believed to be obtained from generations of cultural heritage to be preserved and maintained.